2008
DOI: 10.1111/j.1365-2524.2008.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Constructing resilience: social workers’ understandings and practice

Abstract: Concepts and constructions of resilience have assumed a significant position in contributing to understandings of the psychosocial development of children and young people. This paper examines how concepts of resilience are constructed within the literature, and then explores social workers' perceptions and use of resilience with young people who were 'looked after' or at risk of becoming 'looked after'. It addresses the interface between social workers' views and understandings of the emotional health needs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…The concept of resilience has been developed into a theoretical framework known as the resilience construct (Luthar, Cicchetti, & Becker, 2000;Ungar, 2004) which examines the reasons why many individuals, regardless of the negative factors in their lives, are somehow able to draw upon a range of resources which assist them to deal with negative experiences and situations or "bounce back" from adversity (McMurray, Connolly, Preston-Shoot, & Wigley, 2008). Ungar (2004) suggested that discussions about resilience should not only take into account the internal psychological traits or properties of the individual but also a whole range of external social factors, including gender, ethnicity, and socioeconomic status.…”
Section: The Concept Of Resiliencementioning
confidence: 99%
“…The concept of resilience has been developed into a theoretical framework known as the resilience construct (Luthar, Cicchetti, & Becker, 2000;Ungar, 2004) which examines the reasons why many individuals, regardless of the negative factors in their lives, are somehow able to draw upon a range of resources which assist them to deal with negative experiences and situations or "bounce back" from adversity (McMurray, Connolly, Preston-Shoot, & Wigley, 2008). Ungar (2004) suggested that discussions about resilience should not only take into account the internal psychological traits or properties of the individual but also a whole range of external social factors, including gender, ethnicity, and socioeconomic status.…”
Section: The Concept Of Resiliencementioning
confidence: 99%
“…They suggest that the lack of a theory for the process of resilience development in the social work literature, corresponds with an equally atheoretical approach to applying it among social workers. McMurray et al (2008) point out that Daniel's (2006) study, the only research they identified that explored the utility of resilience theory for child welfare social work, "proposed that social workers had a pre-existing knowledge of resilience theory ... However, the atheoretical discussions from social workers in this study stand in stark contrast to Daniel's research.…”
Section: Resilience Theory In Social Workmentioning
confidence: 67%
“…As scientists in the positivist quantitative tradition, these researchers were interested in factors related to what they defined as measurable resilient outcomes. By the 1990s, these ideas from developmental psychology were being imported into related fields including social work, as researchers sought to operationalise the psychologists' empirical findings for child welfare practice (McMurray et al 2008). Resilience theory's roots in developmental psychology are visible in the continued focus on developmental outcomes that characterises most resilience-related literature published in the United Kingdom.…”
Section: The Evolution Of Resilience Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…McMurray, Connolly, Preston-Shoot, and Wigley (2008) looked at how social workers constructed and utilized the concept of resilience in child welfare practice in the U.K. They found that social workers had difficulty conceptualizing resilience, and linking the concept to practice, and noted that "knowledge of the concept of resilience was generally derived from their everyday understanding rather than a policy-based or theoretical comprehension" (p. 307).…”
Section: Resilience and Child Protectionmentioning
confidence: 99%